ISOLATION, PURIFICATION AND CONFIRMATION OF METALLOTHIONEIN FROM THE LIVER TISSUE OF CADMIUM EXPOSED FRESHWATER FISH, CTENOPHARYNGODON IDELLA - Suresh, Ayothi; Meena, Boominathan; Rose, Sumit; Mani, Ramalingam (International Journal of Current Pharmaceutical Research, 2015)
Objective: Metallothioneins (MTs) are a group of low molecular mass, cysteine-rich proteins with a variety of functions including involvement in metal homeostasis, free radical scavenging, protection against heavy metal toxicity, and metabolic regulation. MT was obtained after purification from cadmium (Cd) exposed fish (Ctenopharyngodon idella) liver tissue using affinity chromatography. While various chromatographic separation methods are available, Affinity chromatography has been reported to be more suitable for separating low molecular weight metal bound proteins like MT. Affinity chromatography involves separating using biochemical mixture based on a highly specific interaction such as that between antigen and antibody, enzyme and substrate, or receptor and ligands. Methods: In the present study, in order to induce optimum MT concentrations in tissues, the experimental fishes were exposed to 5 ppm (which is about half the LC50 for this fish) of CdCl2 for 72 h. Results: The induced MT was isolated and purified by Affinity chromatography and desalting column (Sephadex G-25). Purified MT was evaluated by 15% SDS–PAGE and confirmed by western blot with specific antibodies. Conclusion: MT can be used in bio-monitoring programs as a biomarker of Cd exposure in aquatic environments.